1996
DOI: 10.1164/ajrccm.154.6.8970345
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cat allergy with T-cell reactive peptides.

Abstract: We induced in allergic humans the counterpart of murine experimental T-cell tolerance. T-cell lines from cat-allergic humans were used to map T-cell epitopes for the principal allergen of cat dander, Fel d 1. Two peptides of 27 amino acids each were synthesized to contain the dominant epitopes (ALLERVAX CAT). After a safety trial, we carried out a blinded study of the dose required for efficacy. We randomly divided 95 cat-sensitive patients into placebo, 7.5 micrograms, 75 micrograms, and 750 micrograms groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
191
1
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(199 citation statements)
references
References 0 publications
3
191
1
4
Order By: Relevance
“…Allergen-derived peptides or adapted approaches (LPs, mutated allergens, allergen fragments, etc.) may be of the utmost interest for the therapy of allergic diseases, since peptides with low or absent IgE-binding capacity, but conserved recognition by T cells, can be easily synthesized, and offer a safe alternative to native allergen for specific immunotherapy (14,18,(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-derived peptides or adapted approaches (LPs, mutated allergens, allergen fragments, etc.) may be of the utmost interest for the therapy of allergic diseases, since peptides with low or absent IgE-binding capacity, but conserved recognition by T cells, can be easily synthesized, and offer a safe alternative to native allergen for specific immunotherapy (14,18,(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent the risk of cross-linking of allergen-specific IgE, the use of synthetic peptides containing immunodominant epitopes of allergens has been exploited. In several clinical trials, however, it has been shown that, although some patients showed a reduction of airway symptoms and Th2-associated responses, Fel d I peptide immunotherapy elicited allergic symptoms and late asthmatic reactions in cat-allergic asthmatics (7,8). Moreover, we recently showed that in OVA-sensitized mice, s.c. immunotherapy with the immunodominant T cell epitope OVA 323-339 enhanced both airway hyperresponsiveness (AHR) 3 and eosinophilia upon OVA challenge (9), while an in vitro defined superagonistic analogue of this OVA 323-339 epitope had a beneficial effect (10).…”
Section: The Efficacy Of Immunotherapy In An Experimentalmentioning
confidence: 97%
“…The amino acid sequence (17) and the disulfide bonds as determined by nano-ESI mass spectrometry after tryptic digestion of the E. coli expressed (His) 6 -tagged rFel d 1(2 ϩ 1) fusion protein is shown in Fig. 1.…”
Section: Rfel D 1(2 ϩ 1) Forms Stable Disulfide-bonded Homodimers-mentioning
confidence: 99%
“…Treatment of cat allergy by allergen injections is often employed, but clinical results are, in part, controversial. Because only crude dander extract is available for the treatment of cat allergy (4,5), alternative formulations have been proposed (6,7).…”
mentioning
confidence: 99%